PELATIHAN PEMBUATAN KONTEN WEB DAN BROSUR BAGI KELOMPOK UKM KAYU UKIR DESA SESELA - Terasne, Terasne; Permana, Dira; Hanan, Ahmad; Sudirman, Sudirman; Sumarni, Baiq (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This Community Service Program (PKM) aims to train the Wood Carving UKM group to create Web Content and Brochures in Sesela Village. The partner in this activity is the Chair of the Sesela Village Wood Carving UKM Group. The implementation method used in an effort to achieve the goals in this Community Service activity program was through 3 stages, namely: observation, preparation and evaluation. The results of this activity are 1) the zakir art shop UKM group in Selsela village can understand the benefits of web content and brochures on consumer attention 2) The zakira art shop wood carving UKM group can create their own web content and brochures even though they are still in a simple form and still need assistance. This training can be said to be a success where the craftsmen really expect a follow-up program. The follow-up programs that will be carried out include: marketing handicraft products through an English-language website that has been prepared to make it more attractive to consumers both domestically and abroad.